Lambannya Pertumbuhan Industri Perfilman - Kurnia, Novi (Jurnal Ilmu Sosial dan Ilmu Politik, 2006)
The slow growth of film industry in Indonesia is revealed through historical analysis in this article. This has been stem from state failure in regulating the industry, particularly in regulating monopolistic business groups. Moreover public has not been consolidated and hence not strong enough to encounter with pro business state.